Closure - Management, Journal of Infrastructure & Facility Asset (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Journal of Infrastructure & Facility Asset ManagementVolume 6, Special Issue 3, January 2024 (e) ISSN 2656-8896 (P) ISSN 2656-890XJIFAM, Vol.6, Special Issue 2, January 2024Determination of the Composition of Fly Ash, Bottom Ash and Lime or Cement Mixtures as Road Base Material. Case Study: Road Preservation of Sp. Kereng - Bereng Bengkel – Pilang – Pulang Pisau, Central Kalimantan Mochammad Yusuf Hilman, Noor Endah Mochtar & Soendiarto Excavation Slopes Stability Analysis with Cracked Soil in the Construction of the Serang – Panimbang Toll Road (STA 54+625) Under Maximum Rainfall Condition Wahyu Purnamayoga, Trihanyndio Rendy Satrya, Mahendra Andiek Maulana & Wahyu Supriyo Winurseto Correlation of Initial Soil Density and Maximum Soil Density Under Drying-Wetting Cycles and Their Soil Erodibility Tia Evriana, Trihanyndio Rendy Satrya, Mahendra Andiek Maulana & Wahyu Supriyo Winurseto The Improvement of Existing Slope Reinforcement System and The Design of Alternative Slope Reinforcements Case Study: Lainea-Awunio Road Section Km 98+050 South Konawe Regency, Southeast Sulawesi Province Nadia Kamila, Mohamad Khoiri & Freddy Siagian Title of Paper Slope Stability for Landslide in Road Preservation Working Packages Ende-Wolowaru and Junction-Kelimutu STA 8+425 Frans Andre Sasarari, Yudhi Lastiasih, Herman Wahyudi & Agustinus Junianto JIFAM, Vol.6, Special Issue 1, January 2024Slope Stability Analysis for Landslide in Road Preservation Working Packages Ende - Wolowaru and Junction – Kelimutu Sta 10+475 Fauzan Akbar, Yudhi Lastiasih, Herman Wahyudi & Agustinus Junianto Subgrade Stabilization with Ca(OH)2 Lime to Improve the Physical and Mechanical Properties of Soil (Case Study: The National Road Trengguli – Bts. Kab. Demak/Kudus) Rahmadsyah Rangkuti, Ria Asih Aryani Soemitro, Dwa Desa Warnana, Trihanyndio Rendy Satrya & Yanuar Dwi Putra Comparison of Three Embankment Reinforcement on Soft Soil, A Case Study of Calang – Simpang Peut Road Section Doni Mardian, Indrasurya B Mochtar & Dedy Mandarsyah Effect of Fly Ash and Bottom Ash on Characteristics of Clay Soil (Case Study: National Road Section Demak – Kudus, Indonesia) Alien Maulida Nurtaqwim, Ria Asih Aryani Soemitro, Dwa Desa Warnana, Trihanyndio Rendy Satrya & Yanuar Dwi Putra Existing Design Analysis of Slope Reinforcement on Clayey Soil and Its modified Alternatives (Case Study : Awunio – Lapuko National Road, Southeast Sulawesi) Zahrial Firman R, Mohamad Khoiri & Freddy Siagian